Sugars on dehydrated phospholipid bilayer: A mini review on its protective mechanisms - Zuo Qing; Gao Cai (Frigid Zone Medicine)
Sugars are widely recognized for their ability to stabilize cell membranes during dehydration. However, the precise mechanisms by which sugars interact with lipid bilayers remain unclear. This mini-review synthesizes four key hypotheses explaining sugar-mediated protection of dehydrated bilayers: the Water Replacement Hypothesis (WRH), Hydration Force Hypothesis (HFH), Headgroup Bridging Hypothesis (HBH), and Vitrification Hypothesis (VH). We argue that these mechanisms are not mutually exclusive but instead operate synergistically under different cellular contexts. We propose that these hypotheses are not mutually exclusive but likely operate under different cellular contexts. Future studies should prioritize the development of biologically realistic membrane models—incorporating diverse lipids, proteins, and asymmetric leaflets—to elucidate the exact roles and mechanisms of sugars in membrane stabilization. Such advancements will enhance our understanding of anhydrobiosis and inform cryopreservation strategies for mammalian cells.